PENINGKATAN HASIL BELAJAR LUAS JAJARGENJANG DAN LUAS SEGITIGA DENGAN PENDEKATAN CTL DI KELAS IV SD - Perdana, Dinul Harbi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The purpose of this research to improve learning outcomes and the vast parallelogram area of ​​a triangle with the approach of Contextual Teaching and Learning (CTL) in class IV SDN 47 Parit Panjang Lubuk Basung Agam District. This research was classroom action research (classroom action research). Student learning outcomes in the research cycle I know the average score of 65.3. From the analysis of the second cycle of research to know the average score was 75. Having done the research revealed that the use of CTL approach can improve learning outcomes extensive area of ​​the triangle on the parallelogram and fourth grade elementary school students 47 Parit Panjang Lubuk Basung Agam District. Kata kunci: hasil belajar, matematika, contextual teaching and learning (CTL)